Corona Treatment of Filled Dual-polymer Dispersion Coatings: Surface Properties and Grease Resistance. Issue 4 (May 2017) - Ovaska, Sami-Seppo; Geydt, Pavel; Rinkunas, Ringaudas; Lozovski, Tadeusz; Maldzius, Robertas; Sidaravicius, Jonas; Österberg, Monika; Johansson, Leena-Sisko; Backfolk, Kaj
Dispersion coating layers consisting of hydroxypropylated starch, 0–30 pph of barrier-grade talc and 0–10 pph of styrene-butadiene latex were subjected to both positive and negative direct-current corona treatments utilizing a specially developed dynamic treatment unit. The effects of the surface composition (barrier coating) on the response to the direct current corona treatment were evaluated by measuring contact angles and determining the surface energy. The effects of corona treatment on the properties of the barrier coating were further determined by measuring the contact angle of rapeseed oil and the grease resistance. It was found that the grease resistance of the corona-treated barrier coatings was substantially lower than that of untreated samples, which was ascribed to holes caused by corona discharge strike-through and to chemical changes on the treated surfaces. The corona treatment lowered the surface energy of the coatings, as indicated by an increase in the contact angles of water and rapeseed oil. Changes in the dispersion part of the surface energy were recorded, particularly after positive treatment voltage, whereas a negative discharge led to greater changes in the polar part of the surface energy. X-ray photoelectron spectroscopy (XPS) tests revealed an increase in the proportion of talc at the surface after corona treatment, which indicates a migration caused by the applied electric field. The peak force tapping mode of an atomic force microscope revealed moderate topographical changes in the coatings and a decrease in surface elasticity, supporting the migration of talc particles. In addition, significant changes in the physicochemical properties of the untreated reverse side were observed.